2019
DOI: 10.7554/elife.45644
|View full text |Cite
|
Sign up to set email alerts
|

'Palaeoshellomics’ reveals the use of freshwater mother-of-pearl in prehistory

Abstract: The extensive use of mollusc shell as a versatile raw material is testament to its importance in prehistoric times. The consistent choice of certain species for different purposes, including the making of ornaments, is a direct representation of how humans viewed and exploited their environment. The necessary taxonomic information, however, is often impossible to obtain from objects that are small, heavily worked or degraded. Here we propose a novel biogeochemical approach to track the biological origin of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 88 publications
(135 reference statements)
2
28
0
Order By: Relevance
“…The finding that Spondylus matrices are rather organic-poor is consistent with the data obtained on other cross-lamellar (Agbaje et al, 2019;Demarchi et al, 2015;Marie et al, 2013a;Osuna-Mascaró et al, 2014) and foliated (Pierini et al, 2016) shells; this contrasts to what is observed in organic-rich nacreous and prismatic microstructures (Marie et al, 2009b;Marin et al, 2013;Sakalauskaite et al, 2019). As spondylids represent a bivalve family that emerged rather recently, in the Middle Jurassic (Waller, 2006), our observations corroborate the pioneering idea of Palmer that, in molluscs, the "cost" for making a shell is mostly driven by the "cost" to synthesize the organic matrix (Palmer, 1992); we can argue that evolution was directed to strike a balance between the mechanical properties of a biomineral and the actual "cost" required to produce it.…”
Section: Biochemistrysupporting
confidence: 84%
See 3 more Smart Citations
“…The finding that Spondylus matrices are rather organic-poor is consistent with the data obtained on other cross-lamellar (Agbaje et al, 2019;Demarchi et al, 2015;Marie et al, 2013a;Osuna-Mascaró et al, 2014) and foliated (Pierini et al, 2016) shells; this contrasts to what is observed in organic-rich nacreous and prismatic microstructures (Marie et al, 2009b;Marin et al, 2013;Sakalauskaite et al, 2019). As spondylids represent a bivalve family that emerged rather recently, in the Middle Jurassic (Waller, 2006), our observations corroborate the pioneering idea of Palmer that, in molluscs, the "cost" for making a shell is mostly driven by the "cost" to synthesize the organic matrix (Palmer, 1992); we can argue that evolution was directed to strike a balance between the mechanical properties of a biomineral and the actual "cost" required to produce it.…”
Section: Biochemistrysupporting
confidence: 84%
“…1) Shell matrix proteins are frequently characterized by the presence of repeated low complexity domains (LCDs or RLCDs, frequently found as long poly-Ala/Asp/Ser/Gly blocks (Kocot et al, 2016;Marie et al, 2017;Sakalauskaite et al, 2019), and post translational modifications such as phosphorylation (Du et al, 2018) and glycosylation (Boskey and Villarreal-Ramirez, 2016;Mann and Edsinger, 2014), making the protein sequences difficult to cleave using standard proteases and thus reducing the chance of identification.…”
Section: Proteomicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The colouration and patterning of the molluscan shell and associated biominerals (e.g. pearls) have fascinated human cultures since prehistoric times [510]. The pigmentation of these structures holds not only aesthetic beauty, but can also dictate their commercial value [11–13].…”
Section: Introductionmentioning
confidence: 99%